Short communication: Pre- and postmilking anatomical characteristics of teats and their associations with risk of clinical mastitis in dairy cows (2016)
ABSTRACT: The primary objective of this study was to describe and compare anatomical characteristics of teats before and after machine milking adjusted for parity and teat location (front versus rear). The second objective was to determine if selected milking and anatomical characteristics of teats were associated with occurrence of clinical mastitis. To address objective 1, a cross-sectional study was done to describe and compare teat dimensions before and after milking (n = 1,751 teats from 445 cows). To fulfill objective 2, a case-control study was performed. Quarters having their first case of clinical mastitis in the current lactation from 2 mo before to 2 mo after the day the teats were measured were selected as cases (n = 47), provided no other quarters from that cow were affected by clinical mastitis at that time. Three controls (n = 141) were matched with each case; these were selected from quarters that did not experience any case of clinical mastitis during their current lactation. A conditional logistic regression model was used to determine associations between teat dimensions and occurrence of clinical mastitis. Primiparous and multiparous Holstein cows were enrolled in both studies. As compared with premilking dimensions, postmilking teats were longer and narrower at the barrel and the apex. Significant interactions between teat position and parity were identified for premilking teat length and diameter of the teat barrel. Premilking, teats were longer and wider with increasing parity. Front teats were longer and wider than rear teats premilking. Also during premilking, differences between the front and rear teat were less at increasing parity. Teat apex diameter was greater for premilking teats of cows in parity ≥3 and the apexes of front teats were wider than those of rear teats. Teats enrolled in the case-control study had twice as many clinical mastitis cases in front quarters compared with rear quarters. Premilking diameter of the teat apex was positively associated with risk of clinical mastitis (odds ratio = 1.20 per 1-mm increase in the diameter of the apex of the teat, 95% confidence interval = 1.05–1.37). Milking machine-related changes in teat dimensions had no association with occurrence of clinical mastitis.